Using TSPi and PBL to support software engineering education in an upper‐level undergraduate course. Issue 4 (8th May 2012) - Garcia, I. A.; Pacheco, C. L.
ABSTRACT In recent years, software engineering education has rapidly changed to incorporate more realistic ways of learning. More frequently the software industry requires more skilled and qualified staff; however at the university level students are young, inexperienced, and relatively homogeneous in background and abilities. This article describes an approach that integrates a student teamwork methodology (TSPi) and project‐based learning (PBL) to improve software project managerial skills in undergraduate students. As complementary support, a computational tool, the Teamwork Platform for Software Engineering Education, has been developed to establish an interactive software engineering course with local software industry collaboration. Experimental results show that a set of software metrics was defined to demonstrate performance improvement of 45 students following our approach.© 2012 Wiley Periodicals, Inc. Comput Appl Eng Educ 22:736–749, 2014; View this article online at wileyonlinelibrary.com/journal/cae; DOI 10.1002/cae.21566